Women and Children First: the Gendered and Generational Social-ecology of Smaller-scale Fisheries in Newfoundland and Labrador and Northern Norway - Neis, Barbara; Gerrard, Siri; Power, Nicole (Ecology and Society, 2013)
The resilience of small-scale fisheries in developed and developing countries has been used to provide lessons to conventional managers regarding ways to transition toward a social-ecological approach to understanding and managing fisheries. We contribute to the understanding of the relationship between management and the resilience of small-scale fisheries in developed countries by looking at these dynamics in the wake of the shock of stock collapse and fisheries closures in two contexts: Newfoundland and Labrador, Canada, and northern Norway. We revisit and update previous research on the gendered effects of the collapse and closure of the Newfoundland and Labrador northern cod fishery and the closure of the Norwegian cod fishery in the early 1990s and present new research on young people in fisheries communities in both contexts. We argue that post-closure fishery policy and industry responses that focused on downsizing fisheries through professionalization, the introduction of quotas, and other changes ignored the gendered and intergenerational household basis of small-scale fisheries and its relationship to resilience. Data on ongoing gender inequities within these fisheries and on largely failed recruitment of youth to these fisheries suggest they are currently at a tipping-point that, if not addressed, could lead to their virtual disappearance in the near future.